Gender roles in entrepreneurship education to social entrepreneurial intentions in Vietnam - Nguyen Thuy Lan, Anh; Quoc Lam, Bao; Quynh Duong Nguyen, Anh; Pham, Minh (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
Social enterprises help sustainably develop the national economy by focusing on social values. Social entrepreneurs contribute to significantly reducing unemployment, poverty, and social evils. Therefore, developing entrepreneurship education to increase the number of social entrepreneurs deserves the attention of many countries. Women are also part of society. However, female entrepreneurs make up only one-third of that of men. This study evaluated the differences between gender groups in the relationship between education and social entrepreneurship intention. Data collected from 811 Vietnamese students were analyzed using partial least squares structural equation modeling to assess gender differences. The results show that there is a significant difference between women and men in the formation of social entrepreneurship intentions. Meanwhile, the impact of entrepreneurship education on gender is not clear.